Educação a distância (EAD): a realidade brasileira e as contribuições de Otto Peters - Hickel, Melita (2009)
The here presented PhD thesis is the result of the research by its author, started after her direct promotion for Doctorate, which followed her passing the Qualifying Exam for Master, as well as of notes on activities previously undertaken and directly related to the theme. The research has as subject the modality of education Distance Education (DE), and as main theoretical basis the work of Prof. Dr. Otto Peters and the analysis of the Legislation of Brazil in the area, as well as those of Brazilian DE researchers and a brief presentation of four universities in the state of Rio Grande do Sul. In the first chapter a brief biobibliography of Prof. Peters is presented, alongside some of the main factors present in his work that are of extreme importance for DE. Otto Peters was the founder and first rector of the FernUniversität (FU) in Hagen, Distance University of Germany, which is operating since the beginning of December 1974, being an iconic reference in the area, having contributed and still largely contributing for the development of DE and the credibility and recognition that this modality of education enjoys nowadays. In this chapter are also to be found data registers about the FernUniversität and the interview with Prof. Peters which took place in Hagen. The second chapter focuses on the presentation of the legislation of Brazilian for the modality of education studied, as well as the analysis of some of its most significant and relevant aspects for this work and briefly the proposed work in the area of distance education four universities in the state of Rio Grande do Sul. The third one comprehends a series of questions and reflections pertinent to DE and attempts of answers to them.